(untitled) (Huellas, 2024)
Between the decades of 1960 and 1990, the family dairy farming activity, a fundamental link in the dairy circuit located in the dairy basin in Buenos Aires province, experienced significant transformations. These were driven by the demands of pasteurization, the mechanization of tasks, the railways decline, the automobile transportation growth, the lower labour demand, changes in dairy demand and the expansion of large diversified plants. Within a context of process of productive change, which role did mobility, in terms of infrastructure and practices, play? How did mobility restrict family dairy production? How did (in)accessibility influence? In order to answer these questions that have not deserved enough historiographical attention, this research describes the daily life of dairy farming families in the General Paz district, with the focus placed on mobility practices and the accessibility problems that made their social reproduction difficult in the mentioned period. To do this, a socio-territorial approach will be used and multiple sources will be compiled and analyzed, such as the press, legislation, statistics, maps and interviews.